A Systematic Profiling of the Volatile Compounds in 53 Cerasus humilis Genotypes Using Headspace Solid-Phase Microextraction and Gas Chromatography-Mass Spectrometry - Lingjuan Zhang; Xuanxuan Han; Shuai Zhang; Junjie Du; Jiancheng Zhang; Yu Gary Gao; Pengfei Wang; Xiaopeng Mu (Horticulturae, 2023)
The fruits of Cerasus humilis have a unique and pleasant aroma. In this study, the volatile compounds of ripe fruits of 53 C. humilis genotypes were extracted via headspace solid-phase microextraction (HS-SPME) and identified via gas chromatography coupled with mass spectrometry (GC-MS). In total, 253 volatile compounds were detected, among which esters and terpenoids were the most dominant volatile components. We also found that the total volatiles contents varied significantly among genotypes with different ripening periods, with middle-ripening periods genotypes having higher total volatile content compared to either early- or late-ripening period genotypes. Moreover, genotypes with yellow fruit peels had higher total volatile contents. Our study revealed the volatile profiles of 53 different C. humilis genotypes and their potential linkages with other fruit parameters. These results should help fruit researchers gain a deeper understanding of the biochemical, physiological, and molecular mechanisms of fruit aroma development for high fruit aroma-targeted breeding of fruit cultivars.